2021
DOI: 10.3390/toxins13080513
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin Profile and Phylogeny of Pathogenic Alternaria Species Isolated from Symptomatic Tomato Plants in Lebanon

Abstract: The tomato is one of the most consumed agri-food products in Lebanon. Several fungal pathogens, including Alternaria species, can infect tomato plants during the whole growing cycle. Alternaria infections cause severe production and economic losses in field and during storage. In addition, Alternaria species represent a serious toxicological risk since they are able to produce a wide range of mycotoxins, associated with different toxic activities on human and animal health. Several Alternaria species were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…Our results revealed that both S. globuliferum and S. vesicarium are closely related to Alternaria spp., but phylogenetically they were distinct from each other. This result is consistent with the finding obtained by Habib et al [38].…”
Section: Discussionsupporting
confidence: 94%
“…Our results revealed that both S. globuliferum and S. vesicarium are closely related to Alternaria spp., but phylogenetically they were distinct from each other. This result is consistent with the finding obtained by Habib et al [38].…”
Section: Discussionsupporting
confidence: 94%
“…For each gene, PCR mixture (15 μl) containing approximately 15–20 ng of DNA template, 1.5 μl (10X) PCR solution buffer, 0.45 μl of each primer (10 mM), 1.2 μl dNTPs (2.5 mM), and 0.125 μl of Hot Start Taq DNA Polymerase (1 U/μL; Fisher Molecular Biology, Trevose, Pennsylvania, US) was amplified. Amplification of Alt-a1 and gpd genes was performed with the primer pairs alt-for/alt-rev ( Hong et al, 2005 ), gpd1/gpd2 ( Berbee et al, 1999 ) using PCR reaction parameters as reported by Masiello et al (2019) , CaM gene was amplified using the PCR conditions reported by Habib et al (2021) .…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the above mentioned species, other species have been associated with leaf blight in Tunisia. Ben Chobba et al ( 2013) identified also A. gaisen (included in Alternaria Section) by using ITS1 and ITS4 genes, whereas Namsi et al (2021) identified A. mali, by using ITS, gpd, CaM, and Alt-a1 genes. However, in other studies, A. mali was proposed as synonymous to A. alternata species (Woudenberg et al, 2015), whereas, according to Somma et al (2019), A. mali was phylogenetically more similar to A. gaisen, both species being distinguishable from A. alternata.…”
Section: Species Identificationmentioning
confidence: 99%
“…Genomic DNA was extracted and purified from 2-d-old colonies grown on cellophane disks overlaid on PDA at 25±1°C (Habib et al, 2021).…”
Section: Dna Extractions and Pcr Amplificationsmentioning
confidence: 99%